Prevalence of Overweight and Obesity among Medical Students of Enam Medical College, Savar, Dhaka - Begum, Noortaj; Shila, Jakia Sultana; Mohtarin, Sabreena; Sultana, Sharmin; Parvin, Rukhsana; Khan, Md Aminul Haque (Journal of Enam Medical College, 2021)
Background: Overweight and obesity are recognized as “escalating epidemics” affecting both developed and developing countries. Of the factors contributing to obesity, stress seems to be particularly important as stressful condition leads to irregularity in diet, lack of exercise and addiction. Medical students are exposed to a lot of stress throughout their education. Hence, this study was undertaken to find out the prevalence of overweight and obesity among undergraduate medical students. Objectives: The present cross-sectional study was intended to find out the prevalence of overweight/obesity among medical students of Enam Medical College and its association with their sociodemographic and life-style pattern. Materials and Methods: This cross- sectional study was conducted among medical students in Enam Medical College, Savar, Dhaka from March to July 2017. A total of 283 1st and 2nd year MBBS students were included in the study. After getting permission from college authority and concerned Ethical Committee data were collected using a semi-structured questionnaire containing the variables of interest. Blood pressure and anthropometric measurements (weight and height) were noted. Data were analysed using SPSS (Statistical Package for Social Sciences) version 16.0. Results: In the present study, the prevalence of overweight and obesity was 21.2% and 6.0% respectively. Males were found more overweight or obese (70.1%) compared to females (29.9%) (p=0.041). No other sociodemographic variables were found associated with overweight or obesity. Family history of obesity was observed for evaluation of overweight/obesity among the respondents (p=0.018) although family history of hypertension and/or diabetes did not influence the overweight/ obesity. Systolic and diastolic blood pressures of the overweight/obese group were higher than their normal counterparts (p=0.003 and p=0.002). There was no association between BMI and behavioral variables such as exercise, sleep, entertainment and food behavior. Conclusion: More than one-quarter of the undergraduate medical students are overweight or obese and overweight or obesity are more predominant in males. Overweight and obese students generally have family history of overweight or obesity. Behavioural factors such as taking exercise, time spent on sleep and entertainment and food habit are not associated with BMI. J Enam Med Col 2020; 10(2): 86-92